Antioxidant And Anti-Inflammatory Activities Of Leaves, Calli And Cell Suspension Of Putat (Barringtonia Racemosa) - Behbahani, Mandana (2007)

(untitled)
The medicinal plant of Barringtonia racemosa (Lecythidaceae family) has been used widely in traditional medicine for anti-inflammation and anticancer in Malaysia. The present investigation was carried out to study anti-oxidant and anti-inflammatory effects of leaves, callus, cell suspension and in vitro regenerated shoots and roots of B. racemosa. The results showed that different crude extracts of fully expanded leaf extracts of B. racemosa have a very strong nitric oxide (NO) inhibitory and antioxidant activities. In the Griess assay, non polar extracts such as chloroform and hexane extracts were found to be strong inhibitors of NO at different concentrations (25, 50, 100 and 200 μg/ml) in comparison with polar extract (ethanol extract).Calli were aseptically obtained by placing surface sterilized leaf explants on Woody Plant Medium (WPM) supplemented with different concentrations of 2,4-dichlorophenoxyacetic acid (2,4-D). On the shoot induction medium, the callus induced on the WPM medium containing 2 mg/L (w/v) KIN+0.2 mg/l (w/v) IBA and 2 mg/L (w/v) of KIN + 0.4 mg/L(w/v) of NAA was the most effective, providing high shoot regeneration frequency of 85.6 and 76.5 %, respectively. In addition, the highest number of shoots produced was 8.2 and 6.3 shoots per explant respectively in the medium containing the mentioned plant growth regulators. The rooting percentage and number of roots per shoot which achieved on WPM medium supplemented with 3g/L (w/v) of activated charcoal and 0.8 mg/L (w/v) of IBA were 62 and 5.6 %, respectively. 96 % of the in vitro rooted plantlets with well developed shoots and roots were survived when transferred to soil. Results obtained from this study revealed that B.racemosa is one of the important sources of lycopene. Lycopene has long been recognized as important antioxidants both in vivo and in vitro. Lycopene level was detected at a range of 0.02 to 4.14 mg/g dry weight in in vitro regenerated shoots and roots respectively. Lycopene level was also successfully detected in the callus (0.34 to 2.12 mg/g dry weight) and cell suspension cultures (0.18 to 0.68 mg/g dry weight) under dark and light conditions and the amount was lower than that produced in the intact plant tissues. However, manipulating the physical conditions, feeding of precursor and elicitation managed to increase the lycopene content in cultured tissues. Studies on the effects of the medium composition show that fully strength of the basal Woody Plant Medium and B5 containing 3% (w/v) of sucrose increased the lycopene content in both callus and cell suspension cultures. The precursor-feeding studies revealed that concentrations of 3 mg/L (w/v) of isopentenyl pyrophosphate and 2 to 4 mg/L (w/v) of Mevalonate were preferred for lycopene production. The elicitor studies exhibited that the different elicitors showed distinctive effects on lycopene production. Nevertheless, casein hydrolysate at 10 and 15 mg/l (w/v) was found to be the best in increasing the lycopene production in callus and cell suspension cultures. The study further concluded that there was correlation between anti-oxidant and anti-inflammatory activities and lycopene content in callus, cell suspension and in vitro regenerated organs of B.racemosa.